Topoisomerase II-mediated site-directed alkylation of DNA by psorospermin and its use in mapping other topoisomerase II poison binding sites - Kwok, Yan (The National Academy of Sciences, 1998)
Psorospermin is a plant natural product that shows significant in vivo activity against P388 mouse leukemia. The molecular basis for this selectivity is unknown, although psorospermin has been demonstrated to intercalate into DNA and alkylate N7 of guanine. Significantly, the alkylation reactivity of psorospermin at specific sites on DNA increased 25-fold in the presence of topoisomerase II. In addition, psorospermin trapped the topoisomerase II-cleaved complex formation at the same site. These results imply that the efficacy of psorospermin is related to its interaction with the topoisomerase II–DNA complex. Because thermal treatment of (N7 guanine)–DNA adducts leads to DNA strand breakage, we were able to determine the site of alkylation of psorospermin within the topoisomerase II gate site and infer that intercalation takes place at the gate site between base pairs at the +1 and +2 positions. These results provide not only additional mechanistic information on the mode of action of the anticancer agent psorospermin but also structural insights into the design of an additional class of topoisomerase II poisons. Because the alkylation site for psorospermin in the presence of topoisomerase II can be assigned unambiguously and the intercalation site inferred, this drug is a useful probe for other topoisomerase poisons where the sites for interaction are less well defined.